2014
DOI: 10.5455/pmb.1-1356302532
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sleep and Touch Therapy Accompanied By Music and Aromatherapy on the Impact Level of Fibromyalgia, Fatigue and Sleep Quality in Fibromyalgia Patients

Abstract: ÖZET AMAÇ: Bu çalışmanın amacı, müzik ve aromaterapi eşliğinde yapılan uyku ve dokunma tedavisinin fibromiyalji hastalarında fibromiyalji etki düzeyi, yorgunluk ve uyku kalitesi üzerine etkilerini saptamaktır. Literatürde fibromiyalji hastalarında yorgunluk ve uyku şikâyetlerinden bahsedilmesine ve bunları önlemeye yönelik uykuyu düzenlemek ve yorgunluk hassasiyetini azaltmak için bazı alternatif metodlar kullanılmasına rağmen, Türkiye'de fibromiyalji hastalarına yönelik hastanelerde herhangi bir program bulun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
(18 reference statements)
1
5
0
Order By: Relevance
“…The results of the present study suggest that lavender may positive effect on insomnia symptom of women. This is in accordance with previous study which reported improvement of insomnia through aromatherapy and massage therapy for fibromyalgia (Demirbağ & Erci, 2014). Many studies have found that aromatherapy improves psychological symptoms such as anxiety, depression and induces more relaxed states in young and middleaged women (Buckle, 2003).…”
supporting
confidence: 92%
“…The results of the present study suggest that lavender may positive effect on insomnia symptom of women. This is in accordance with previous study which reported improvement of insomnia through aromatherapy and massage therapy for fibromyalgia (Demirbağ & Erci, 2014). Many studies have found that aromatherapy improves psychological symptoms such as anxiety, depression and induces more relaxed states in young and middleaged women (Buckle, 2003).…”
supporting
confidence: 92%
“…The most common FSS reported by our FMS patients was non-restful sleep (92.3%) and the least reported was intestinal complaints (32.7%), similar to the previous studies. [27,28,50] Most of the complaints screened in the FSS can also be seen in many psychiatric disorders, particularly depression. Determination of whether these symptoms are due to FMS itself or are result of a psychiatric disorder, is only possible after detailed physical and psychiatric examinations.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1381 participants were included in this meta-analysis. The 19 studies were published in Iran [ 15 22 ], Turkey [ 23 26 ], Korea [ 27 ], South Korea [ 28 , 29 ], Japan [ 30 , 31 ], China [ 32 ], or the United States [ 33 ] from 2012 to 2021. The essential oils used as interventions were lavender, citrus, and mixed essential oils.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, different types of population experience varying degrees of fatigue, and each has its own scale. The participants were female in six RCTs [ 26 , 28 , 29 , 31 33 ] included in our analysis, and many of the clinical trials focused on women's health in using aromatherapy, for example, for menopausal symptoms, delivery, and dysmenorrhea [ 45 ]. However, there was no evidence that supported the prevalence or effects of aromatherapy use with respect to gender.…”
Section: Discussionmentioning
confidence: 99%